2020
DOI: 10.1002/lsm.23220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fractional CO2 Laser, Promestriene, and Vaginal Lubricant in the Treatment of Urinary Symptoms in Postmenopausal Women: A Randomized Clinical Trial

Abstract: Background and Objectives Evaluating the efficacy of the fractional CO2 laser, promestriene, and vaginal lubricant to treat urinary symptoms in women with genitourinary syndrome of menopause. Study Design/Materials and Methods We conducted a randomized clinical trial with 72 postmenopausal women aged 50 years or older. The participants were randomized to one intervention each in three treatment groups fractional CO2 laser, promestriene, and vaginal lubricant. Urinary symptoms were assessed prior to treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 40 publications
0
80
0
Order By: Relevance
“…In fact, the use of local estrogens is supported by the evidence of superiority over placebo in several trials, for both clinical and cytological outcomes [46,47]. About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the use of local estrogens is supported by the evidence of superiority over placebo in several trials, for both clinical and cytological outcomes [46,47]. About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50]. In addition, another study showed that the fractional CO 2 laser was effective in women dissatisfied with previous local estrogens [52].…”
Section: Discussionmentioning
confidence: 99%
“…A small but statistically significant improvement in ICIQ-OAB scores was described. No adverse effects were reported during the study period [10]. The results of Aguiar et al show a small but statistically significant difference between the intravaginal fractional CO 2 laser and topical oestrogen groups for treating OAB symptoms related to GSM [10].…”
mentioning
confidence: 97%
“…No adverse effects were reported during the study period [10]. The results of Aguiar et al show a small but statistically significant difference between the intravaginal fractional CO 2 laser and topical oestrogen groups for treating OAB symptoms related to GSM [10]. Once more the sample size was too small to draw any long-term conclusions for the efficacy of vaginal laser use for the treatment of OAB symptoms.…”
mentioning
confidence: 97%
See 1 more Smart Citation